Sistem Informasi Akuntansi Arus Kas Sebagai Pengendali Kas Dengan Metode Accrual Basis - Eni Endaryati; Sri Wahyuning; Meylia Putri Mawardani (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
Accounting Information System for cash receipts and disbursements is a very important managerial function, because the majority of companies need information about cash receipts and payments, as well as RM. Sampurna needs information about cash receipts and disbursements as cash controllers. The accrual basic method is one method that can assist the cash control process. This method is a method that makes accounting records when the transaction occurs even though the money has not been received, making it easier for the owner to control the cash. And with an accounting information system for cash receipts and disbursements on an acrual basis as cash control that has been used has been able to support performance at RM Sampurna, thus helping companies manage financial data and validate the resulting data can be justified.